STRATEGIC APPROACH TO ASSESSING THE EFFICIENCY OF AGRICULTURAL AND TOURISM BUSINESS IN THE ECONOMY OF SERBIA - Orlandić, Milja; Novović, Milan; Petrović, Dragana (Economics of Agriculture, 2025)
The authors will present a strategic approach to assessing the performance of agriculture and tourism in the Republic of Serbia. The purpose of the analysis is to determine which of the given economic activities has better economic performance and, accordingly, has a greater impact on the economic growth and development of the Republic of Serbia. The research covered the financial statements of large and medium-sized enterprises in the areas being analyzed. The results of the ratio analysis indicate that both activities jointly contribute to the economic growth and development of the Republic of Serbia. When it comes to determining bankruptcy, the Altman Z` score model has been adapted for developing economies. According to this model, agriculture and tourism, at the level of calculated average values, operate in a zone of moderate risk, which is a golden mean and a good indicator of their business performance.